Shintoism in Japan - Kadhim, Mohammed; Salman , Hussein (Al-Adab Journal, 2025)
Japan has always been ambiguous in its religious beliefs and references, as this research attempts to identify the most prominent elements of Japanese culture, as it is Japan’s first religion (Shintoism). Shintoism has always been known as the worship of nature, as it is a religion affected by environmental fluctuations such as earthquakes, floods and storms, and for the purpose of protection from this reality, the Japanese try to worship multiple gods called (kami), each of which is specialized in an environmental / natural reality that establishes his worship to seek his satisfaction and not be angry, thus survival. This applies to a wide range of human needs, not only natural disasters from which he tries to survive, but also tries to succeed in work, succeed in school, get a partner, and other human needs, so the Japanese individual performs a set of religious practices and rituals. The founding history of Shintouism saw the development of two Shintoya scriptures, the first (kojiki) and the second (nihongji). These two books were written for various reasons, including political and social reasons, this was done under the auspices of an empire, to write the Japanese myth, it is a tale that interprets the primitive time, and describes the method of birth of the gods, the way the Japanese Isles were created and ruled, and the gods’ association with the imperial family biologically. But the most prominent dynasty remains the breed (Amaterasu), from whose descendants the dynasty of Japanese emperors appeared, which was the reason for the dominance of many emperors to rule Japan, the most prominent and famous of which was (Meiji), who ruled Japan with an iron fist. Kojiki became an important book during his reign that was established in Japanese schools, until the emperor became a god. But this ended completely after Japan’s surrender in World War 2, where the United States imposed on Japan to keep religion away from government institutions, not to teach Kojiki in schools, and to give absolute freedom to the Japanese people to adopt the religion that is appropriate for them, which helped the return of Buddhism and Christianity. Shintoism became as private companies, they finance themselves by selling prayers, collecting money from people to participate in religious rituals, making a lot of money selling amulets and souvenirs, and organizing weddings led by specialized monks.